Investigation of the effect of gasoline premixed ratio and engine load on the combustion and exhaust emission characteristics of an RCCI Engine - Firat, Mujdat; Altun, Sehmus; Okcu, Mutlu; Varol, Yasin (Gazi Univ, Fac Engineering Architecture, 2022)
In this study, the effect of using biodiesel and petroleum-based diesel mixture and gasoline on combustion and exhaust emission characteristics in a single cylinder diesel engine modified to operate in RCCI mode was experimentally investigated. In the study, B20 mixture fuel, which consists of 20% biodiesel and 80% petrol-based diesel mixture by volume, was sprayed directly into the cylinder as a high reactivity fuel while gasoline as a low reactivity fuel was injected into the suction channel. The experiments were carried out in five different premixed ratios as 0% (conventional diesel combustion), 15%, 30%, 45% and 60%, and under different load conditions with constant engine speed. According to the data obtained, it was determined that the maximum pressure value in the cylinder decreased with the increase of the mixture ratio under RCCI conditions at 0% and 20% load, and increased at 40% and 60% load. Under RCCI conditions, when the engine was running at no load and at low loads such as 20%, NOx emission was reduced, but an increase was observed with the increase of engine load. However, it has been determined that the increase in the mixture ratio at all loads reduces the smoke opacity, which was by 96% at 60% load and with the use of 60% mixing ratio. Apart from an decrease in CO emission under RCCI conditions at 60% load, it was observed that CO and unburned HC emission levels increased with the increase of the mixing ratio at all loads under RCCI conditions.
Bir RCCI motorun yanma ve egzoz emisyon karakteristikleri üzerinde benzin ön karışım oranı ve motor yükünün etkisinin incelenmesi
Keywords: RCCI; biodiesel; diesel; gasoline; combustion